Effect of Incorporation of Nano-Hydroxyapatite and Nano-Zinc Oxide in Resin Modified Glass Ionomer Cement on Metal Bracket Debonding - Mohsen Nuri Sari; Nafiseh Rahmani; Mehdi Araghbidi Kashani; Gholamreza Eslami Amirabadi; Ali Akbari Sari; Elahe Seyedtabaii (Islamic Dental Association of Iran, 2015)
Background and Aim: Use of fluoride releasing materials to decrease the risk of demine-ralization around orthodontic brackets would be reasonable as an adhesive for bracket bonding only if they provide acceptable shear bond strength (SBS). The aim of this study was to evaluate the SBS of resin-modified glass ionomer cements (RMGICs) modified by nano-zinc oxide (NZnO) and nano- hydroxyapatite (NHA) in comparison with composite resins. Materials and Methods: In this experimental study, 80 extracted human premolars were used. The teeth were randomly divided into 4 groups as follows: Group 1: Trans bond XT as a control group, Group 2: RMGIC (Fuji II LC), Group 3: RMGIC with5% NHA and Group 4: RMGIC with2% NZnO. After etching the enamel, brackets were bonded. The SBS was measured for each group. The percentage of adhesive remnants on the enamel surface was quantified using the adhesive remnant index (ARI).The data were analyzed using one-way ANOVA and the Kruskal Wallis test. Results: According to the results of ANOVA, no significant difference was found in theSBS of groups (p=0.075). The mean shear bond strength in groups 1 to 4 was 15.43 ± 4.61, 14.95 ± 4.34, 17.97 ± 3.65 and 17.08 ± 3.59, respectively. According to the Kruskal-Wallis test, there was no significant difference in ARI score among the groups (p=0.413). Conclusion: The amount of SBS was similar among all groups and addition of NZnO and NHA particles had no negative effect on SBS of RMGIC. Less than half the adhesive re-mained on the enamel surface after bond failure in all groups.